Accelerated method of identification of bacteria and micromycetes in hemocultures in children using multiplex PCR in real time - V. N. Chebotkevich; E. A. Martens; S. V. Sidorenko; E. Е. Kiseleva; S. S. Bessmeltsev (Журнал инфектологии, 2019)
Objective: To evaluate the effectiveness and clinical significance of an accelerated, method, for the identification of microorganisms in blood, cultures in children using real-time multiplex PCR.Materials and methods: A total of 72 blood, samples were obtained, from 62 children aged. 3 months to 16 years. The identification of the isolated cultures, according to the proposed, method, was carried out in real-time PCR and. also using classical culture microbiological methods.Results: Based, on the frequency of detection and. the clinical significance of pathogens isolated from children, a panel of test systems was formed to identify them, by means of real-time PCR. It was shown that the effectiveness of the developed, method, for identification, of bacteria and. micromycetes by real-time PCR was 86,7% as compared, with the microbiological method. A significant reduction in the time of identification, of pathogens (from 48 hours to 5—7 hours) was demonstrated. In addition, the use of this method, allows, at the same time, to identify a number of antibiotic resistance genes (in particular, the genes of acquired, carbapenemases and. methicillin-resistant staphylococci).Conclusion: The developed, method, with real-time PCR for detecting and identifying microorganisms in the blood has shown its effectiveness, clinical significance and. the possibility of using it for pediatric patients. Its use significantly shortens the time frame for obtaining results and, thus, allows timely initiation, of etiotropic therapy.